Opinion: Faster, higher, stronger - how sports research can help win gold medals - Keogh, J.; Gowthorp, L. (The West Australian, 2024)
Australia's Olympic success, driven by innovations in training and techniques, highlights the importance of marginal gains like starts, underwater phases and quick turns. The 2024 Paris Olympic Games saw several standout performances, especially female athletes, who claimed 33 of 53 medals. Such a result suggests initiatives like the Female Performance and Health Initiative and a record $283 million in federal funding are paying dividends. Furthermore, with strategies like "Win Well" promoting both performance and athlete well-being, Australia is building a strong foundation for the 2028 and 2032 Olympic Games.